A two-phase heat transfer test facility for ammonia: construction and testing - Keltner, Erik (Kansas State University, 2005)
Recent world events are motivating the United States Government to invest in the development of Directed Energy Weapons (DEW). One defense contractor developing the technology, Raytheon Missile Systems Company, is addressing the cooling requirements. To this end, Raytheon has proposed some two-phase (liquid and vapor) heat transfer devices capable of dispersing the high energy densities associated with DEW. The Kansas State University Mechanical and Nuclear Engineering Department has been contracted to characterize the performance of the devices using ammonia as the working fluid. To this end, an Ammonia Test Chamber was reconfigured to perform the experiments. The chamber is now configured to deliver liquid ammonia at saturation pressures ranging from 45 to 115 psia, a sub-cooled liquid temperature of -25oC, and mass flow rates ranging from 0.01 to 0.03 kg/s. The Ammonia Test Chamber can absorb heat loads of up to 5000 W. Measurements of the Critical Heat Flux (CHF) of the device ranged from 173 W/cm2 to 488 W/cm2. This data agrees characteristically with published correlations of CHF values, however the correlations predict lower magnitudes.
Keywords: Ammonia; Two-phase; Impinging; Jets; Heat transfer; Engineering, Mechanical (0548)